Documentation for Food and Fertilizers Export Restriction Tracker: Tracking export policy responses affecting global food markets during crisis - Laborde Debucquet, David; Mamun, Abdullah (International Food Policy Research Institute, 2022)
In response to the Ukraine-Russia crisis, as it was the case in previous crisis (e.g.COVID19 pandemic), some governments have implemented export restrictions and other trade policy measures to secure their food supply and protect inputs for their farmers. This behavior can increase global food prices, with consequences including the exacerbation of hunger and income losses for producers in exportrestricting countries. Intergovernmental organizations and other actors need current information on food trade policy to curb detrimental reactive policy and enable cooperation. To address this need, we provide the Food & Fertilizer Export Restriction Tracker, an extension of the previous work of food trade policy tracking done during COVID-19 pandemic. Gathering data from sources including the media, national governments, expert input, we provide up-to-date information on food trade policies implemented during the crisis and the likely magnitude of their effects.